Evaluation of pre-game hydration status, heat stress, and fluid balance during professional soccer competition in the heat - Aragon-Vargas, L. F.; Moncada-Jimenez, J.; Hernandez-Elizondo, J.; Barrenechea, A.; Monge-Alvarado, M. (European Journal of Sport Science, 2009)
In this study, we assessed initial hydration status (stadium arrival urine specific gravity), fluid balance (pre- and post-game nude body weight, fluid intake, urine collection), and core temperature changes (pre-game, half-time, post-game) during a professional soccer game. We monitored 17 male players (including goalkeepers) between arrival at the stadium and the end of the game (3 h), playing at 34.9°C and 35.4% relative humidity, for an average wet bulb globe temperature (WBGT) heat stress index of 31.9°C. Data are reported as mean±standard deviation (range). Initial urine specific gravity was 1.018±0.008 (1.003-1.036); seven players showed urine specific gravity = 1.020. Over the 3 h, body mass loss was 2.58±0.88 kg (1.08-4.17 kg), a dehydration of 3.38±1.11% body mass (1.68-5.34% body mass). Sweat loss was 4448±1216 ml (2950-6224 ml) versus a fluid intake of 1948±954 ml (655-4288 ml). Despite methodological problems with many players, core temperatures = 39.0°C were registered in four players by half-time, and in nine players by the end of the game. Many of these players incurred significant dehydration during the game, compounded by initial hypohydration; thermoregulation may have been impaired to an extent we were unable to measure accurately. We suggest some new recommendations for soccer players training and competing in the heat to help them avoid substantial dehydration.